Analysis Of The Technical Ability Of Shooting and Passing of Extracurricular Futsal Students At Nur Hidayah Kartasura Senior High School - Mubarak, Usaid Syahrul; Indarto, Pungki; Nurhidayat (UNIB Press, 2025)
This study aims to evaluate the shooting and passing technique abilities of students who take part in futsal extracurricular activities at Nur Hidayah Kartasura Senior High School. A quantitative approach was employed, using a test method to collect data. The population comprised 40 students, while a purposive sampling technique was applied to select a sample of 25 students. The primary variables examined were the students’ competencies in performing shooting and passing techniques in futsal. The findings revealed that in the shooting technique test, 60% (15 students) achieved the “fair” category, 28% (7 students) reached the “good” category, and 12% (3 students) fell into the “poor” category. Regarding the passing technique, 56% (14 students) were classified as “good,” 36% (9 students) as “very good,” and 8% (2 students) as “poor.” These results indicate that most students possess adequate technical abilities. Nevertheless, continuous and well-structured training programs remain essential to further enhance their performance and ensure sustained skill development over time.